Low-Income Housing Finance in Colombia - Maria Angelica Arbelaez; Carolina Camacho; Deisy Johanna Fajardo (Inter-American Development Bank (IDB), 2011)
This paper explores the role played by policy instruments in access to housing finance by low-income households. It also analyzes the impact of housing credit and subsidies on both the quality of life and the quality of dwelling of the beneficiaries. Using the Quality of Life Surveys conducted in Colombia in 2003 and 2008, the study finds that policy instruments aimed at easing access of low-income households to affordable housing such as subsidies and loan guarantees have played a modest role in increasing the use of mortgages as a source of funding. Despite this, subsidies were found to have had a significant impact on both the quality of dwelling and the quality of life. Therefore, this paper suggests promoting the use of both instruments by improving their design and targeting.
Keywords: D61; H81; I30; I31; I32; I38; O17; R20; R28; R31; R38; 330